Application-Centric Analysis of IP-based Mobility Management Techniques - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2001)
This paper considers three applications—VoIP, mobile Web access and mobile server-based data transfers—and evaluates the applicability of various IP-based mobility management mechanisms. We first survey the features and characteristics of various IP mobility protocols, such as MIPv4, MIPv6, MIP-RO, SIP, CIP, HAWAII, MIP-RR and IDMP, and then evaluate their utility on an application-specific basis. The diversity in the mobility-related requirements ensures that no single mobility solution is universally applicable. We recommend a hierarchical mobility architecture. The framework uses our Dynamic Mobility Agent (DMA) architecture for managing intra-domain mobility and multiple application-based binding protocols for supporting inter-domain mobility. Thus, we recommend SIP as the global binding protocol for VoIP applications and MIPv4/MIPv6 as the global binding mechanism for the mobile server scenario.